The Emotional Freedom Technique Reduces the Anxiety of the Elderly with Hypertension - Wahyuningsih Safitri; Intan Wahyu Dhamayanti; Mellia Silvy Irdianti; Febriana Sartika Sari (GLOBAL HEALTH SCIENCE GROUP, 2021)
One of the aging processes that experienced by the elderly in cardiovascular system health problems is hypertension. A relatively long treatment and recovery cause anxiety. The emotional freedom technique is a non-pharmacological method for dealing with anxiety. To find out the effect of the emotional freedom technique on the anxiety level in elderly with anxiety. Method: Research design is a pretest and posttest quasi-experiment with a control group. This study was conducted in Sragen village area. The sampling technique used purposive sampling. The total sampling is 144 respondents, divided into two groups namely 72 respondents of a treatment group and 72 respondents of the control group. The tool of the study was a questionnaire of Hamilton Rating Scale for Anxiety to rate the level of anxiety experienced by elderly with hypertension. The data were analyzed by using Wilcoxon test and Mann Whitney test. Wilcoxon test showed p value 0.000< 0,0, there was a significant effect on the anxiety level of the elderly with hypertension and Mann-Whitney test obtained p value 0.042, showing that the group given the emotional freedom technique treatment was effective in reducing the anxiety level compared to the control group. Emotional freedom technique is effective to reduce the anxiety level of elderlies with hypertension.